Randomized controlled trial of robotic-assisted versus conventional laparoscopic fundoplication: 12 years follow-up - Lang, Franziska; Huber, A.; Kowalewski, Karl-Friedrich; Kenngott, Hannes Götz; Billmann, Franck; Billeter, Adrian; Fischer, Lars; Bintintan, V. V.; Gutt, Carsten N.; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2022)
Numerous reports have addressed the feasibility and safety of robotic-assisted (RALF) and conventional laparoscopic fundoplication (CLF). Long-term follow-up after direct comparison of these two minimally invasive approaches is scarce. The aim of the present study was to assess long-term disease-specific symptoms and quality of life (QOL) in patients with gastroesophageal reflux disease (GERD) treated with RALF or CLF after 12 years in the randomized ROLAF trial.